The pope at war: the secret history of Pius XII, Mussolini, and Hitler - Kertzer, David I. (Random House, 2022)
"When Pope Pius XII died in 1958, his papers were sealed in the Vatican Secret Archives, leaving unanswered questions about what he knew and did during World War II. Those questions have only grown and festered, making Pius XII one of the most controversial popes in Church history, especially now as the Vatican prepares to canonize him. In 2020, Pius XII's archives were finally opened, and David I. Kertzer--widely recognized as one of the world's leading Vatican scholars--has been mining this new material ever since, revealing how the pope came to set aside moral leadership in order to preserve his church's power. Based on thousands of never-before-seen documents not only from the Vatican, but from archives in Italy, Germany, France, Britain, and the United States, The Pope at War paints a new, dramatic portrait of what the pope did and did not do as war enveloped the continent and as the Nazis began their systematic mass murder of Europe's Jews. The book clears away the myths and sheer falsehoods surrounding the pope's actions from 1939 to 1945, showing why the pope repeatedly bent to the wills of Hitler and Mussolini"--